Effects of glyphosate herbicide ingestion on kidney function in rats on a balanced diet - Bruno Reis Moreira Nacano; Marcia Bastos Convento; Andréia Silva de Oliveira; Rafaela Castino; Bianca Castino; Clara Versolato Razvickas; Eduardo Bondan; Fernanda Teixeira Borges (Brazilian Journal of Nephrology, 2023)
Abstract Introduction: Glyphosate is the most widely used herbicide worldwide and in Brazil. There is currently increasing concern about the effects of glyphosate on human health. The Brazilian Institute for Consumer Protection showed data on the presence of glyphosate in some of Brazil’s most consumed ultra-processed products. Currently, regulations on the upper limit for these residues in ultra-processed foods have yet to be established by the National Health Surveillance, and ultra-processed food consumption is independently associated with an increased risk of incident chronic kidney disease. Methods: Since an unbalanced diet can interfere with kidney function, this study aims to investigate the effect of daily intake of 5 mg/kg bw glyphosate in conjunction with a balanced diet and the possible impact on renal function in rats. Kidney function, kidney weight, markers of renal injury, and oxidative stress were evaluated. Results: There was a decrease in kidney weight. The main histopathological alterations in renal tissues were vacuolation in the initial stage and upregulation of the kidney injury marker KIM-1. Renal injury is associated with increased production of reactive oxygen species in mitochondria. Conclusion: This study showed changes in the kidney of rats exposed to a balanced diet with glyphosate, suggesting a potential risk to human kidney. Presumably, ultra-processed food that contain glyphosate can potentiate this risk. The relevance of these results lies in drawing attention to the need to regulate glyphosate concentration in ultra-processed foods in the future.